Pengaruh Model Pembelajaran Discovery Learning terhadap Kemampuan Berpikir Kreatif Matematis Siswa: Sebuah Tinjauan Literatur Sistematis dan Analisis Bibliometrik - aisha artanti; hasanuddin (Program Studi Tadris Matematika Fakultas Tarbiyah Institut Agama Islam Al-Qolam Malang, 2025)
This study aims to systematically analyze the impact of the Discovery Learning model on students' mathematical creative thinking skills through a systematic literature review approach and bibliometric analysis. This study follows seven stages of the Systematic Literature Review (SLR), namely identifying research needs, formulating research questions, searching for literature with relevant keywords, selecting articles with inclusion and exclusion criteria, extracting primary data, thematic and bibliometric analysis, and reporting findings. Several articles from various national and international accredited journals published between 2017–2024 were analyzed using VOSviewer software for visual mapping. The results of the study indicate that the Discovery Learning model contributes positively to the development of mathematical creative thinking skills, especially in the aspects of fluency, flexibility, uniqueness, and elaboration. Bibliometric analysis also shows an increasing trend of research on this topic in the last decade. This study recommends further exploration of the use of technology in discovery learning and longitudinal studies across educational levels.